PERAN TEORI BELAJAR KOGNITIVISTIK TERHADAP PROSES BERPIKIR PESERTA DIDIK - Fika Rahmayani; Nuril Ma’rifah; Moh. Zein Chilmi; M. Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study looks at how cognitive learning theory helps students better understand how they learn. Cognitivist learning theory focuses on the mental activities inside our heads, like thinking, remembering, understanding, and solving problems, as the main parts of how we learn. This study talks about what cognitive learning theory means, highlighting important people like Jean Piaget, Jerome Bruner, David Ausubel, and Robert M. Gagne and different kinds of cognitive theories that have come about in education. This study also looks at the cognitive learning approach, which aims to help students improve their active thinking skills. It does this by using methods like meaningful learning, discovery learning, and organizing information. The study's results show that using cognitive theory is very important for helping students gain a better understanding, enhance their critical thinking abilities, and grow their problem-solving skills. So, cognitive learning theory can be a helpful basis for building a learning process that is more meaningful and focused on the students.